2017
DOI: 10.1155/2017/7421842
|View full text |Cite
|
Sign up to set email alerts
|

A Hot Spots Ignition Probability Model for Low-Velocity Impacted Explosive Particles Based on the Particle Size and Distribution

Abstract: Particle size and distribution play an important role in ignition. The size and distribution of the cyclotetramethylene tetranitramine (HMX) particles were investigated by Laser Particle Size Analyzer Malvern MS2000 before experiment and calculation. The mean size of particles is 161 μm. Minimum and maximum sizes are 80 μm and 263 μm, respectively. The distribution function is like a quadratic function. Based on the distribution of micron scale explosive particles, a microscopic model is established to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The accidental ignition of explosive charges in the launch environment is one of the primary reasons for bore bursts, the mechanism of which has been the focus of considerable research on the launch safety of explosive charges [3,4]. Many scholars [5][6][7][8][9][10] have examined the stress, action time, and hot-spot generation of an explosive charge in the launch environment, finding that factors influencing accidental ignition are the particle size, pores, bottom gaps, cracks, and other defects associated with the explosive charge [11][12][13][14][15]. Wu et al [11] analyzed the influence of particle size on the ignition process and showed that the ignition time increases monotonically with decreasing particle size (50-200 μm).…”
Section: Introductionmentioning
confidence: 99%
“…The accidental ignition of explosive charges in the launch environment is one of the primary reasons for bore bursts, the mechanism of which has been the focus of considerable research on the launch safety of explosive charges [3,4]. Many scholars [5][6][7][8][9][10] have examined the stress, action time, and hot-spot generation of an explosive charge in the launch environment, finding that factors influencing accidental ignition are the particle size, pores, bottom gaps, cracks, and other defects associated with the explosive charge [11][12][13][14][15]. Wu et al [11] analyzed the influence of particle size on the ignition process and showed that the ignition time increases monotonically with decreasing particle size (50-200 μm).…”
Section: Introductionmentioning
confidence: 99%